1995
DOI: 10.1042/bj3080057
|View full text |Cite
|
Sign up to set email alerts
|

Specific degradation of troponin T and I by μ-calpain and its modulation by substrate phosphorylation

Abstract: The degradation of troponin (Tn) subunits by calpain was studied by incubating either isolated cardiac Tns or myocardial cryosections with two different calpain isoenzymes isolated from rat skeletal muscle. Western-blot analysis with monoclonal antibodies against TnI and TnT showed that mu-calpain was at least ten times more active than m-calpain in degrading TnI and TnT both in vitro and in situ. TnC was completely resistant to both proteinase forms. Phosphorylation by cyclic AMP-dependent protein kinase (PKA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
102
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(109 citation statements)
references
References 27 publications
(32 reference statements)
7
102
0
Order By: Relevance
“…cMyBP-C AllPϩ was also highly resistant to the peptide cleavage associated with ischemia (17). Similar data have been obtained for PKA-mediated cardiac troponin I phosphorylation, which significantly reduced troponin I proteolysis (28). These data provide further support for the hypothesis that sarcomere-based gain of function provides long-term benefits in heart failure (29), although additional studies are needed to understand fully the role that cMyBP-C phosphorylation might play in cardioprotection.…”
Section: Discussionsupporting
confidence: 72%
“…cMyBP-C AllPϩ was also highly resistant to the peptide cleavage associated with ischemia (17). Similar data have been obtained for PKA-mediated cardiac troponin I phosphorylation, which significantly reduced troponin I proteolysis (28). These data provide further support for the hypothesis that sarcomere-based gain of function provides long-term benefits in heart failure (29), although additional studies are needed to understand fully the role that cMyBP-C phosphorylation might play in cardioprotection.…”
Section: Discussionsupporting
confidence: 72%
“…24 Previously, it has been shown that the calcium-dependent protease calpain I can cause different degradations of the troponin complex. 22,25 In the present work, degradation of TnT in the rabbit was prevented by MDL-28.170, a membrane-permeating inhibitor of calpain I. 18 Despite prevention of TnT-degradation with MDL-28.170, the acute diastolic dysfunction still developed.…”
Section: Hydroxyl Radical Exposure and Myofilament Responsivenessmentioning
confidence: 91%
“…Although from a biochemical point of view it is possible that calpain I proteolyses TnI as well as TnT, 25 the mechanisms of the species dependency remain open and are important to be addressed in future studies. However, this does not impact on the central conclusion of the present study, ie, that myofilament alterations are not involved in the acute diastolic dysfunction; in presence of calpain I this myofilament proteolysis can be inhibited, but the acute diastolic dysfunction is still present.…”
Section: Hydroxyl Radical Exposure and Myofilament Responsivenessmentioning
confidence: 99%
“…Similar to concomitant phosphorylation, protein degradation can also occur simultaneously. Selective degradation of TnI and TnT by calpain was detected both in vitro [124] and in vivo after ischemia/ reperfusion [31,125]. Interestingly, phosphorylation of TnI by PKA and PKC changed its susceptibility to calpain-induced degradation conversely [124].…”
Section: Interactions Between and Within Different Types Of Protein Mmentioning
confidence: 99%
“…Selective degradation of TnI and TnT by calpain was detected both in vitro [124] and in vivo after ischemia/ reperfusion [31,125]. Interestingly, phosphorylation of TnI by PKA and PKC changed its susceptibility to calpain-induced degradation conversely [124]. As another example of communications between different types of modifications, degradation of MLC-2 and TnC after ischemia/reperfusion could be prevented by the addition of an oxygen-free radical scavenger [46].…”
Section: Interactions Between and Within Different Types Of Protein Mmentioning
confidence: 99%